KARAKTERISASI KITOSAN CANGKANG LANDAK LAUT JENIS Tripneustes Gratilla DENGAN DEASETILASI KONSENTRASI NaOH YANG BERBEDA - Hadi, Pratiwi; Bahri, Syamsul; Rasulu, Hamidin (Universitas Khairun, 2024)
The population of sea urchin Tripneustes gratilla in Tidore City, North Maluku Province, is very abundant and rich in chitosan sources. This variety of sea urchin can be used as a food source. Waste from sea urchin shells has not been utilized properly and efficiently, so one effective alternative that can be used to handle piles of shell waste is to process the chitin content into chitosan. This research aims to determine the characteristics of sea urchin shell chitosan from the use of different NaOH concentrations in the deacetylation process. This research method used a one-factor Completely Randomized Design (CRD) with 5 different NaOH concentration treatments at a heating time of 90 minutes, a temperature of 105oC and 3 repetitions, so that 15 experimental units were obtained. The data obtained were analyzed using the ANOVA test and if the differences showed results that had a real effect then a Least Significant Difference (BNT) further test was carried out at the Î± = 5% level. The results of the study showed that the effect of adding different concentrations of NaOH had a significant effect on the physical characteristics in the form of yield, color. (L a b), molecular weight, and degree of deacetylation. Chemical characteristics of water content, ash content, fat content and protein content. The characteristics of chitosan analyzed by FTIR showed a high deacetylation degree value of Ëƒ 80%, SEM morphology showed that each treatment had a mixed form, and the XRD results of chitosan had a crystalline structure with the main peak at an angle of 20 = 19o â€“ 24o with the highest angle aimed at 20 = 24o . If seen from the ranking results of the best treatment, namely C5 (NaOH concentration 18%) with a physical properties yield value of 60.16%, L color 60.16, a value 90.23 and b value 5.91, molecular weight 197.00 kDa, and degree of deacetylation 97.80%, chemical properties include content water 10.19%, ash content 1.17%, fat content 0.48%, and protein content 2.58%.Â Keywords: chitosan, NaOH, Tripneustes gratilla, deacetylation